2017
DOI: 10.1038/bmt.2017.203
|View full text |Cite
|
Sign up to set email alerts
|

Impact of choice, timing, sequence and combination of broad-spectrum antibiotics on the outcome of allogeneic haematopoietic stem cell transplantation

Abstract: Recent data link the incidence of intestinal GvHD (iGvHD) after allogeneic haematopoietic stem cell transplantation (aSCT) to exposure with piperacillin-tazobactam or imipenem-cilastatin. To assess relevance of timing, duration, sequence and combination of antibiotic treatment in this setting, we applied a time-dependent model to our aSCT cohort. Patients from the prospective Cologne Cohort of Neutropenic Patients (CoCoNut) undergoing aSCT from January 2007 to April 2013 were included into a time-dependent mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
2
19
0
1
Order By: Relevance
“…On the other hand, use of carbapenem for greater than 7 days was not associated with poor OS and high NRM. Farowski et al reported that cumulative antibiotic exposure was related to the incidence of acute GVHD. Long‐term administration of carbapenem may cause loss of beneficial anaerobic bacteria for regulating alloreactive response, such as Clostridia and Blautia .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, use of carbapenem for greater than 7 days was not associated with poor OS and high NRM. Farowski et al reported that cumulative antibiotic exposure was related to the incidence of acute GVHD. Long‐term administration of carbapenem may cause loss of beneficial anaerobic bacteria for regulating alloreactive response, such as Clostridia and Blautia .…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, we recently confirmed exposure to these antibiotic classes as an independent risk factor for intestinal GvHD in allo-HCT patients. 18 Concordantly, other studies have demonstrated these antibiotics as risk factors of CDI. 15,19 Yet other studies have confirmed a link between development of CDI and intestinal GvHD.…”
Section: Discussionmentioning
confidence: 62%
“…In comparison with all above‐mentioned RCTs, it must be noted that our study results are based on real‐life observational patient data outside the highly controlled environment of a clinical trial. To the authors’ knowledge, our data were extracted from one of the world’s largest single‐centre cohorts of haematological patients who are at high risk developing healthcare‐associated infections 22–24 …”
Section: Discussionmentioning
confidence: 99%